2013
DOI: 10.1021/om400711d
|View full text |Cite
|
Sign up to set email alerts
|

Bis(diisopropylphosphinomethyl)amine Nickel(II) and Nickel(0) Complexes: Coordination Chemistry, Reactivity, and Catalytic Decarbonylative C–H Arylation of Benzoxazole

Abstract: The facile one-step synthesis of five new bis(diisopropylphosphinomethyl)amine ligands RN(CH2DIP)2 (DIP = diisopropylphosphine, R = Me–, iPr–, PhCH2–, 2-ThCH2–, and 2-FuCH2−) based on the use of the air-stable phosphonium salt [DIP(CH2OH)2]Cl is presented. The phosphonium salt cleanly reacts with primary amines to afford amine-bridged bisphosphine ligands with variable backbone substitution in good yields. These DIP ligands are useful model systems for their chiral bisphospholane analogues. The coordination ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 101 publications
0
11
1
Order By: Relevance
“…Next, the scope of various benzoxazoles was also evaluated. As our expectation both 5-methylbenzoxazole and 5-chlorobenzoxazole generally underwent the arylation to give the corresponding products in very good yields ranging from 82 to 95% except the case of 4-uorobenzaldehyde and 4-hydroxybenzaldehyde whose resulting arylated products were only obtained in signicantly diminished yields of 70-75% (Table 3, entries [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. For the benzoxazole bearing a nitro substituent, the lower yields of arylation products with various aldehydes were recorded even though harsher conditions (higher temperature for prolonged reaction time) were employed ( Table 3, entries [31][32][33][34][35][36][37].…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Next, the scope of various benzoxazoles was also evaluated. As our expectation both 5-methylbenzoxazole and 5-chlorobenzoxazole generally underwent the arylation to give the corresponding products in very good yields ranging from 82 to 95% except the case of 4-uorobenzaldehyde and 4-hydroxybenzaldehyde whose resulting arylated products were only obtained in signicantly diminished yields of 70-75% (Table 3, entries [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. For the benzoxazole bearing a nitro substituent, the lower yields of arylation products with various aldehydes were recorded even though harsher conditions (higher temperature for prolonged reaction time) were employed ( Table 3, entries [31][32][33][34][35][36][37].…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 90%
“… 21 Additionally, the requirement of high-cost palladium catalysts and other expensive additives also prevents the palladium-catalyzed cross-coupling procedure from being employed in large-scale synthesis. 22 Recently, the replacement of palladium by other transition metals, such as bis(diisopropylphosphinomethyl)amine nickel( ii ) and nickel(0) complexes, 23 metal–organic frameworks, 24,25 Cu/Fe system, 26 CeO 2 /Fe 3 O 4 , 27 CuCN(PPh 3 ) 2 , 28 and Ni(COD) 2 , 29 has been investigated. These direct arylation methods have received much attention due to their advantage of avoiding the use of stoichiometric amounts of expensive organometallic reagents or additives.…”
Section: Introductionmentioning
confidence: 99%
“…In the latest years much attention has been focused on nickel organometallics both for catalytic applications and academic purposes, e. g. unusual oxidation states, low coordination numbers, stoichiometric activation of small molecules, bioinorganic model systems. Mononuclear square-planar Ni(II) complexes stabilized by bi-or tridentate ligands 100 A tetradentate trianionic ligand has been used by G.-H. Lee and collaborators in order to build up a model for the Methyl CoMreductase, which displays an unusual pentacoordinate environment for the metal in the +3 oxidation state (Scheme 16a). 103 The relevance of Ni(III) carbyl species supported by amido-pyridine N,N,N,N ligands in cross coupling reactions has also been established.…”
Section: Groupmentioning
confidence: 99%
“…Complex 7 was also observed in the attempted couplings with the cationic complex 6 ( Figure S3), highlighting a general behaviour for these CpNi(NHC) species thereof. Interestingly, although C(2)-benzoxazolyl or benzothiazolyl complexes are often proposed as intermediates in C-H/C-X couplings between heteroarenes and aryl, alkenyl or alkyl electrophiles [5,10,12,14,16,17,19,20,22,23], they remain very rare. We are indeed aware of only four related PCN-Pd [39][40][41] and NNN-Ni [23] pincer species, which have been isolated with a benzothiazolyl ligand and demonstrated to be intermediates in similar couplings.…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…The recent trend to use 3d transition metal catalysts, that is driven by economic and environmental concerns, has led to a re-assessment of nickel's reactivity [1][2][3][4]. In particular, nickel catalysts have emerged as promising candidates for C-H bond functionalization [5][6][7][8], and nickel-catalyzed reactions between (hetero)arenes and aryl halides [9][10][11][12], phenol derivatives [13][14][15][16][17][18], aryl or alkenyl esters [19][20][21] or even alkyl halides [22,23] have been shown to be reliable atom-economical alternatives to palladium-catalyzed cross-couplings. In this context, we have recently reported that the unsaturated T-shaped nickelacycle 1, that bears a mono-anionic C,C-NHC-cyanoalkyl chelate (NHC = N-heterocyclic carbene), shows moderate activity for the coupling of benzothiazole with aryl iodides (Scheme 1) [24].…”
Section: Introductionmentioning
confidence: 99%